Improving propagation lengths of ultraviolet surface plasmon polaritons on thin aluminium films by ion milling. (13th December 2018) - Wardley, W P; Rodríguez-Fortuño, F J; Zayats, A V; Dickson, W
Abstract: Ultraviolet plasmonics provides several benefits over the visible or infrared spectral range. The intrinsic optical properties of aluminium make it the best material for ultraviolet-based plasmonic systems, but in practice thin aluminium films exhibit higher roughnesses than those of other metals grown by physical vapour deposition. This roughness increases scattering losses, decreasing surface plasmon polariton propagation length. Here we experimentally demonstrate a method for improving the optical quality of aluminium films using an ion milling post-deposition processing step to reduce surface roughness. The propagation length of surface plasmon polaritons has been measured in the ultraviolet spectral range using grating pairs fabricated by focused ion beam milling. The propagation length for as-deposited films has been compared with films produced by normal incidence and oblique angle milling. An increase in propagation length of about 20% was observed for both normal and oblique angle milling.